The Effect of Rebozo Technique Complementary Therapy on Reducing the Intensity of Labor Pain in the First Active Phase - Hasana, Indah Ayu Nur; Sari, Dwinda; Zuniawati, Lilis; Diniah, Sanamiatu (An Idea Health Journal, 2024)
The birth of the fetus, placenta, and membranes from the uterus through the birth canal is a labor process caused by uterine contractions, the effect of cervical dilatation (opening or thinning) of the cervix, and descent of the fetal head. The intensity of the pain depends on the strength of the contraction and the pressure that arises during the contraction. When the pain cannot be overcome, labor will last a long time and will cause many indications that endanger the lives of the mother and fetus. The aim of this study was to determine the effect of complementary therapy with the Rebozo technique on reducing the intensity of labor pain during the first active phase. This research used a quasi- experiment with a pre and post test one group control design with a sample size of 30 respondents. Data was collected through observation sheets which were then analyzed using the Wilcoxon test. The results of this study obtained a significant value of 0.000 < significant result of 5% (p-value = 0.000-0.05) so it can be concluded that H1 is accepted, which means there is an influence of the use of complementary therapy using the rebozo technique on reducing the level of labor pain in the first stage of the active phase.